Experiences of healthcare for mothers of children with ongoing illness, living in deprived neighbourhoods health and place. (September 2021) - Satherley, Rose-Marie; Wolfe, Ingrid; Lingam, Raghu
Abstract: Purpose: While the association between socioeconomic deprivation and children's poor health is clear, the complex pathways linking socioeconomic deprivation with access to care and health inequalities are less well understood. This analysis sought to understand the root cause of these inequalities by exploring how mothers living in deprived neighborhoods support their sick children, and their experiences with primary care. Methods: Interview transcripts from eight mothers, living in socioeconomically deprived neighborhoods, were analyzed using interpretative phenomenological analysis. Results: Participants described their experiences in three distinct themes. Each theme highlights the importance of the mother's agency, voice, and power in supporting their child's health, and the crucial role played by the health system in addressing, maintaining, or reinforcing health inequalities. Participants used several strategies to address these health inequalities, which included fighting against the health system, using past experiences to explain health needs, and support from friends and family. Conclusion: Although the health system is an essential resource to support families, encounters with primary care may fail to address health inequalities and may therefore exacerbate existing health inequalities for families living in deprived neighborhoods, irrespective of health system financing and ability to pay. Highlights: Associations between socioeconomic deprivation and children's poor health are clear. Complex pathways linking deprivation and poor health are poorly understood. Mother's worked hard to address their children's health needs. Health encounters may fail to address or exacerbate existing health inequalities.